Heterogeneous catalysis of transesterification of jatropha curcas oil over calcium–cerium bimetallic oxide catalyst - Teo, Siow Hwa; Rashid, Umer; Yap, Taufiq Yun Hin (Royal Society of Chemistry, 2014)
A series of heterogeneous basic catalysts (mixed oxides of Ca and Ce) with different molar ratios were synthesized via a conventional co-precipitation process using a highly alkaline carbonate salt. Moreover, investigation was conducted batchwise for the transesterification of crude Jatropha curcas oil (JCO) with methanol at 65 °C and 1 atm pressure. The bimetallic oxides possess high thermal stability, since X-ray diffraction (XRD) proved that the crystalline phases present in mixed oxide catalysts were preserved well as pure oxide even up to 900 °C. The co-precipitation synthesis method provided better interaction between vacancies created by the substitution of calcium (Ca) and cerium (Ce) at pH 11. Moreover, the combination of Ca and Ce reduced the temperature maxima and increased the basicity of catalysts, which exhibited better catalytic activity compared with bulk catalysts (CaO and CeO2). The influences of the Ca/Ce atomic ratio in the mixed oxide catalyst, methanol–oil molar ratio, catalyst amount and reaction time on the fatty acid methyl ester (FAME) content were studied. The suitable molar ratio of Ca-to-Ce was 1, and with the optimum conditions of 4 wt% catalyst dosage and 15% methanol–oil molar ratio, a fatty acid methyl ester (FAME) content of 95% was achieved over CaO–CeO2 catalyst at 65 °C. Moreover, the CaO–CeO2 catalyst shows substantial chemical stability and could be reused at least 4 times without major loss in its catalytic activity.